The Palgrave Literary Dictionary of Robert Browning - Garrett, Martin. author. aut Link
XIX, 224 p.
Keywords: This literary dictionary provides a concise reference guide to Robert Browning. Alphabetical entries cover his revolutionary poetics, drama, long narrative poems, writing on relations between the sexes, and translation and adaptation from classical works. Browning was keenly aware of contemporary politics, especially French and Italian, and his reading was vast and esoteric, his subjects drawn from medieval and Renaissance history and art history, newspapers, even advertisements. He knew Carlyle, George Eliot, George Sand, Thackeray, the Rossettis, Hawthorne and Henry James, and had complex and difficult relationships with Dickens and with the tragic actor William Charles Macready. He was more intimately associated with Tennyson, and above all with Elizabeth Barrett Browning, whose work, character and opinions were one of the most significant influences on him. The dictionary also explores his changing critical reputation: an obscure, generally badly received or ignored young writer; a public figure and much anthologised poet in whose honour a Browning Society was founded in 1881; after another period of neglect, an experimental poet, psychologically sensitive, and the subject of a wide range of scholarly editions and discussion. Martin Garrett is an independent scholar whose other contributions to this series are on Byron (joint winner of the Elma Dangerfield Prize of the International Association of Byron Societies for 2011), P.B. Shelley, Mary Wollstonecraft Shelley and Samuel Taylor Coleridge. Other work on the nineteenth century includes, for Palgrave, A Romantics Chronology, 1780-1832 (winner of the 2017 CILIP Knowledge and Information Management Information Resources Award), and for the British Library Writer’s Lives series, volumes on Byron, Mary Shelley and the Brownings. He has also worked on Beowulf, Renaissance literature and drama, and cultural and literary guides to Greece, Italy, Provence, the Loire, Oxford and Cambridge. .